1991
DOI: 10.1159/000173394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endothelin on the Renal Microcirculation of the Split Hydronephrotic Rat Kidney

Abstract: We have examined the effects of endothelin (ET) on the renal microcirculation by in vivo microscopy using the model of the split hydronephrotic rat kidney. ET, a potent vasoconstrictor peptide synthesized by vascular endothehal cells, showed marked and long-lasting effects on glomerular blood flow and vessel diameters in various segments of the renal vascular bed. Intravenously applied ET (100 ng/min/kg) increased systemic blood pressure from 123 ± 7 to 156 ± 4 mm Hg, decreased glomerular blood flow by 70%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
1
19
1
Order By: Relevance
“…This finding is contrary to the data of Fretschner et al (1991) who examined the effect of endothelin-l in the split hydronephrotic kidney model. They demonstrated that the response to endothelin-1 was attenuated by a competitive leukotriene antagonist.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is contrary to the data of Fretschner et al (1991) who examined the effect of endothelin-l in the split hydronephrotic kidney model. They demonstrated that the response to endothelin-1 was attenuated by a competitive leukotriene antagonist.…”
Section: Discussioncontrasting
confidence: 99%
“…Edwards et al showed that rabbit efferent and afferent arterioles constrict in response to ET-1 and ET-2 (ECm -1 nM) while ET-3 is significantly less potent (35). Similarly, in the hydronephrotic rat kidney both efferent and afferent arterioles constricted in response to topical or lumenal administration of ETs, however, the afferent arteriole may be more sensitive (36)(37)(38). Other investigators have demonstrated the ability of ET to alter glomerular filtration rate and renal vascular resistance in vivo (1).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Loutzenhiser et al (27) reported that, in the isolated perfused hydronephrotic kidney, ET-1 was a po tent vasoconstrictor of the afferent arterioles with a threshold vasoconstriction response at a dose of 0.01 nM, whereas it had a lesser effect in reducing the efferent arteriolar diameter. Fretschner et al (28) used a split hydronephrotic rat kidney model and found that in travenous ET-1 (100 ng/kg/min) induced elevated sys temic blood pressure, decreased glomerular blood flow and preferentially constricted larger preglomerular vessels such as the arcuate artery. However, to our knowledge, no direct demonstration of the involvement of the affer ent or efferent arterioles in normal kidneys has been made to date; the studies cited above were carried out in special ized kidneys, such as the hydronephrotic kidney.…”
Section: Discussionmentioning
confidence: 99%